Tax Management Strategies in Mergers and Acquisitions: Case Studies in the Financial Industry - Nia Marlina (Golden Ratio of Taxation Studies, 2023)
This qualitative literature review explores tax management strategies in mergers and acquisitions (M&A) transactions within the financial industry. The research aims to elucidate the multifaceted nature of tax considerations in M&A transactions and the diverse range of strategies employed by companies to optimize financial outcomes, mitigate risks, and promote sustainable value creation. Through systematic data collection from academic journals, books, and reputable databases, followed by thematic analysis and synthesis, the study investigates the implications of tax management practices from theoretical and managerial perspectives. Key findings highlight the pivotal role of tax considerations in decision-making processes, deal structures, and post-transaction integration plans. The integration of environmental, social, and governance (ESG) considerations into tax management frameworks emerges as a significant trend, reflecting a broader shift towards responsible corporate governance and regulatory compliance. The research underscores the importance of interdisciplinary collaboration and ongoing research in advancing knowledge and understanding in this critical area of corporate finance and governance. The findings contribute to the development of evidence-based practices and informed policy decisions, fostering sustainable growth and value creation in the financial industry.